Traditional Tibetan Medicine in Cancer Therapy by Targeting Apoptosis Pathways - Tang, Ce; Zhao, Cheng-Cheng; Yi, Huan; Geng, Zang-Jia; Wu, Xin-Yue; Zhang, Yi; Liu, Ya; Fan, Gang (Frontiers in Pharmacology, 2020)
Cancer is a leading cause of death around the world. Apoptosis, one of the pathways of programmed cell death, is a promising target for cancer therapy. Traditional Tibetan medicine (TTM) has been used by Tibetan people for thousands of years, and many TTMs have been proven to be effective in the treatment of cancer. This paper summarized the medicinal plants with anticancer activity in the Tibetan traditional system of medicine by searching for Tibetan medicine monographs and drug standards, and reviewing modern research literatures. 40 species were found to be effective in treating cancer. More importantly, some TTMs (e.g., Cordyceps sinensis, Phyllanthus emblica and Rhodiola kirilowii) and their active ingredients (e.g., cordycepin, salidroside and gallic acid) have been reported to possess anticancer activity by targeting some apoptosis pathways in cancer, such as Bcl-2/Bax, caspases, PI3K/Akt, JAK2/STAT3, MAPK, and AMPK. These herbs and natural compounds would be potential drug candidates for the treatment of cancer.